Achieving the idea of Zero Solid Waste City for Jammu through ISWM (Integrated Solid Waste Management) (International Journal of Innovative Research in Engineering & Management, 2022)
The idea of the city is dynamic and steadily  evolving. The present utilization-driven society delivers a  colossal volume of waste consistently. The over-consuming  society per capita squanders age is generally higher in high consuming urban communities in contrast with low consuming urban areas. Changing as of now over consuming urban communities into zero-waste urban  communities is tested. The idea of the zero-waste urban  communities incorporates a 100 percent reusing of city  strong waste and a 100 percent recuperation of all assets  from squandered materials. The expanding issue of strong  waste in Indian urban communities has become one of the  most immovable ecological monetary and social issues  today. Expansion in the volume of waste created by  metropolitan occupants, change in the nature of waste  creation and the removal strategy for squandering gathered  are the main pressing issue. The present paper is a  methodology that examines the issue of strong waste and  fosters zero squander. It endeavors to uncover the issues  worried about strong waste in Jammu. It centers on the  issues recognized in various writing for strong waste. The  paper has been separated into three segments. Area one  chats on the current situation of strong waste. Segment two  do writings audits and makes sense of their finding the  paper at long last attempts to integrate the zero-waste city  thought for Jammu.
Keywords: Waste generation; Waste composition; Integrated Solid Waste Management; Zero Waste